An Excerpt-based Approach to Thematic Identification and Patterns in Armah’s The Beautyful Ones Are Not Yet Born - Yemisi Mulikat Famakinwa (Journal of Pragmatics Research, 2026)
Recently, literary works have enjoyed global recognition, especially among scholars who are interested in both the language use and literary devices therein. Literary works thus have varying ideas and experiences which shape the outcome of the literary work or piece, and talk more about the background of the writer. Hence, African writers in their literature reflect their culture and experiences. Data for this study are sourced from three thematic statements that capture succinctly the three central themes in Armah’s “The Beautyful Ones Are Not Yet Born.” It is worth knowing that the three thematic statements are the same as the three selected sentence excerpts in the novel. With insight drawn from postcolonialism(literature) and Systemic Functional linguistics(grammar), the study avers that themes in both language/grammar and literature provide information. Findings show that thematic statements or sentence excerpts contain certain lexical items that, coincidentally, serve as yardsticks in determining the location of themes in grammar. This is the point of convergence between the theme in language/grammar and literature. The study concludes that themes in both language and literature are partly determined by the occurrences of certain lexical items, which may be thematised, especially in thematic statements/sentence excerpts that capture the literary themes to basically infer meaning.